2019
DOI: 10.1097/ncq.0000000000000350
|View full text |Cite
|
Sign up to set email alerts
|

Using Continuous Vital Sign Monitoring to Detect Early Deterioration in Adult Postoperative Inpatients

Abstract: cVSM demonstrated detection of early signs of patient deterioration to prevent FTR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 10 publications
1
38
0
Order By: Relevance
“…Five studies (N=1308) have been published about the ViSi Mobile (Sotera Wireless; Table 1 ) [ 39 , 40 , 51 , 59 , 60 ]. This device is worn on the wrist, upper arm, or chest, and it measures HR, RR, BP, SpO 2 , and skin temperature ( Table 2 ) [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies (N=1308) have been published about the ViSi Mobile (Sotera Wireless; Table 1 ) [ 39 , 40 , 51 , 59 , 60 ]. This device is worn on the wrist, upper arm, or chest, and it measures HR, RR, BP, SpO 2 , and skin temperature ( Table 2 ) [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Feasibility outcomes: Patients reported the wristband as big or heavy. Four studies reported the perceptions of the health care professionals [ 39 , 51 , 59 , 60 ]. Nurses mentioned that this device had a short battery life and poor connection but it reported better insight into the vital signs [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47][48] Monitoring devices used were specified except in Cavallini et al 46 Vital signs monitored were specified in all except Pearl et al 49 All studies in this group only included nonacute and non-high-risk patients from general medical or surgical wards. 29,[44][45][46][47][48][49][50][51] Association with clinical parameters All five studies in Group A demonstrated clinically relevant information can be derived from data obtained through multi-parameter CoNiM. There were three main themes: patient information; predictive information; and diagnostic information.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Mortality. There was reduced mortality in patients with CoNiM in five studies 29,45,46,49,51 except Langhorne et al 47 Langhorne et al 47 included 'early mobilisation' as a separate intervention; therefore, half of the control population and half of the CoNiM population were also enrolled in 'early mobilisation'. The heterogenous population compounded by a small sample size (n ¼ 32) may have skewed the results.…”
Section: Impact On Clinical Outcomementioning
confidence: 99%